Calcitonin gene-related peptide (CGRP) receptor antagonists: Heterocyclic modification of a novel azepinone lead. (1st July 2021) - Luo, Guanglin; Jiang, Xiang-Jun; Chen, Ling; Conway, Charles M.; Gulianello, Michael; Kostich, Walter; Keavy, Deborah; Signor, Laura J.; Chen, Ping; Davis, Carl; Whiterock, Valerie J.; Schartman, Richard; et al.
Graphical abstract: Abstract: In our efforts to identify orally bioavailable CGRP receptor antagonists, we previously discovered a novel series of orally available azepinone derivatives that unfortunately also exhibited the unwanted property of potent time-dependent human CYP3A4 inhibition. Through heterocyclic replacement of the indazole ring, we discovered a series of heterocycle derivatives as high-affinity CGRP receptor antagonists. Some of them showed reasonable oral exposures, and the imidazolone derivatives that showed good oral exposure also exhibited substantially reduced time-dependent CYP3A4 inhibition. Several compounds showed strong in vivo efficacy in our marmoset facial blood flow assay with up to 87% inhibition of CGRP-induced activity. However, oral bioavailability generally remained low, emphasizing the challenges we and others encountered in discovering clinical development candidates for this difficult Class B GPCR target.